2021
DOI: 10.18331/brj2021.8.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Yeast cell factories for sustainable whey-to-ethanol valorisation towards a circular economy

Abstract: Cheese whey is the major by-product of the dairy industry, and its disposal constitutes an environmental concern. The production of cheese whey has been increasing, with 190 million tonnes per year being produced nowadays. Therefore, it is emergent to consider different routes for cheese whey utilization. The great nutritional value of cheese whey turns it into an attractive substrate for biotechnological applications. Currently, cheese whey processing includes a protein fractionating step that originates the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 132 publications
(218 reference statements)
0
4
0
Order By: Relevance
“…Cultures are also less prone to contaminations, as they ferment at an acidic pH. S. cerevisiae is considered the favorite species for ethanol production because of its high ethanol yield in media with glucose and ethanol tolerance, and is expected to play a central role in multi-waste valorization approaches [47]. However, its main drawback is its incapacity to ferment the xylose that is released during hydrolysis pretreatment of lignocellulosic biomass [2].…”
Section: Discussionmentioning
confidence: 99%
“…Cultures are also less prone to contaminations, as they ferment at an acidic pH. S. cerevisiae is considered the favorite species for ethanol production because of its high ethanol yield in media with glucose and ethanol tolerance, and is expected to play a central role in multi-waste valorization approaches [47]. However, its main drawback is its incapacity to ferment the xylose that is released during hydrolysis pretreatment of lignocellulosic biomass [2].…”
Section: Discussionmentioning
confidence: 99%
“…One promising technology is the use of natural or engineered microbial biocatalysts, such as bacteria [ 16 18 ] or yeasts [ 19 ], to ferment lactose into ethanol fuel. Although advances in strain performances have been proposed and examples of industrial implementation have also been reported, the dairy waste-to-ethanol conversion technology still needs improvements to guarantee its wide adoption, based on the requirements of different bioeconomic models [ 15 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…and a source of value-added products such as organic acids, bacterial cellulose, polymers, bioethanol, etc. [5,6] In addition, bioethanol produced mostly from plant biomass, such as starchy and cellulosic substrates [7,8] shows considerable promise because to its renewable nature. This alternative fuel has the potential to partially substitute fossil fuels and reduce the greenhouse effect by emitting low levels of carbon.…”
Section: Introductionmentioning
confidence: 99%